Bridging the electricity saving intention-behavior gap: A German field experiment with a smart meter website - Mack, Birgit; Tampe-Mai, Karolin; Kouros, Jens; Roth, Frederick; Taube, Oliver; Diesch, Eugen (Energy research & social science, 2019)
We investigated whether a combination of prompted commitment, implementation information, and guided process monitoring would facilitate bridging the intention-behavior gap in electricity saving. In a neighborhood of new housing, user interaction with a smart meter web portal was analyzed and the effect of portal usage on electricity consumption was evaluated. The information architecture of the web portal was designed following principles derived from a stage model of self-regulated behavioral change. The design focused on prompting commitment to saving tips and supporting their implementation. Users that committed themselves to at least one saving tip were higher in pre-baseline goal intention than users that did not. The act of committing to saving tips, together with continued self-monitoring of the process of tip implementation, was predictive of a significant saving effect. Thus, for motivated users techniques inducing commitment to action and guiding towards implementation of the action plan seem effective in generating electricity savings.